EFFECTIVENESS OF ZAKAT, INFAK, AND SHADAQOH MANAGEMENT AT BAZNAS USING ANALYTICAL NETWORK PROCESS (ANP) - Vemy Suci Asih; Ichasan Fajar (Gunung Djati Conference Series, 2024)
The aim of this study is to evaluate and assess the effectiveness of Zakat, Infak, and Shadaqoh (ZIS) management at BAZNAS Bandung Regency. This evaluation is crucial as ZIS serves both as an act of worship and a form of muamalah for every Muslim. The research employs a quantitative approach using the Analytical Network Process (ANP) to identify priority issues and solutions in managing ZIS funds at BAZNAS Bandung Regency. Data for this study were collected through several stages: conducting in-depth interviews with practitioners, distributing questionnaires to two practitioners, creating an ANP network using Super Decision software, and finally prioritizing the issues and solutions. The findings indicate that ZIS fund management at BAZNAS Bandung Regency is not yet effective. Key issues include management practices at BAZNAS, social media engagement, and government involvement. Respondents suggested that BAZNAS should enhance its accountability and transparency in socialization efforts, collaborate with other entities, utilize resources more effectively, improve management practices, educate and support existing personnel to better leverage social media for promoting and advertising BAZNAS, and advocate for local government regulations and revisions to ZIS management policies.